Comparative Analysis of Pid, I-Pd and Fractional Order Pi-Pd for a Dc-Dc Converter - Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2022)
This article presents the design of fractional order PI-PD (FOPI-PD) controller for maintaining the output voltage of a buck converter. Initially, some conventional controllers were adapted, and these controllers introduced the overshoot and large settling time. Therefore, a FOPI-PD has been adapted to overcome the above limitations. The advantage of the FOPI-PD controller is that the error passes through the proportional and integral rather than all the controller gains, which reduces the overall control action. Further, the efficacy of the controllers is investigated in different simulation studies. The results show that the fractional order PI-PD controller significantly enhances the settling time in the presence of different load levels and controller disturbances. © 2022 IEEE.